Effect of Ambient Temperature on Ignition Delay and Biodiesel Derived from Algae - Khalid, Amir (International Journal of Integrated Engineering, 2018)
Global warming and energy crises have increased the awareness about eco-friendly fuels and also accelerated the search of alternative fuels. Biodiesel is defined as methyl esters of long chain fatty acids derived from vegetable oils or animal fats or similar which conform to ASTM D6751 specifications for use in diesel engines. However, low temperature combustion mode has attracted widespread attention in particulate matter and NOx emissions reduction simultaneously. Thus, this paper focuses on experimental investigation for the influence of ambient temperature on ignition delay and emission with different types of biodiesel. A Rapid Compression Machine (RCM) is used for simulated the diesel combustion as similar in the real diesel engine. Besides, two types of biodiesel blends, B2 (2 vol%) such as Algae and Jatropha biodiesel were tested on RCM at injection pressure of 130 MPa under different ambient temperatures from 750 K to 1100 K. The experimental results were compared with Palm-Oil biodiesel with blending ratio of 5%, 10% and 15%. Nevertheless, the result indicated that the ignition delay is slowed when ambient temperature is increased. These phenomena can be explained by the thermal properties of fuels. Ignition delay is found to be slower if premixed combustion process is reduced and also higher ambient temperature due to the increased in fuel ignitibility. The emission of NOx increased as the ambient temperature increased to cause highly combustion temperature.Â